Organic acid content and Antimicrobial Properties of Eleiodoxa conferta Extracts at Different Maturity Stages - Seri Intan Mokhtar; Nur Ain Abd Aziz (Universiti Malaysia Kelantan, 2015)
Eleiodoxa conferta water extracts at different maturity stages were shown to contain three types of organic acid which are oxalic, ascorbic and malic acids by HPLC analysis. The content of oxalic acid concentration was the highest at young stage (1.33 gml -1 ) followed by mature stage (1.26 gml-1 ) and ripe stage at 1.23 gml-1 . Malic acid content decreased during ripening from 1.38 gml-1 to 1.07 gml-1 . The concentration of ascorbic acid remained constants during the fruit ripening. When antimicrobial activity of the extract was tested against several bacteria it was observed that the activity decreased as the fruit ripen. Highest diameter of inhibition zone was recorded against Escherichia coli by the young fruit extract at 15.3 mm. MIC of 0.063 gml-1 exhibit by the young fruit extract was helpful in controlling the growth of Gram negative bacteria, E. coli. However, 0.063 gml-1 concentration of extract from mature fruit is shown to regulate the growth of Gram positive bacteria, Staphylococus aureus.